(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The African Achatina fulica is a land snail introduced to Ecuador for commercial purposes, but it has become as a plague, and is affecting densely populated urban areas. This study aims to determine the prevalence of endoparasites in specimens of A. fulica from Mata de Cacao, Los Rios Province. One hundred specimens of A. fulica were examined from a playground (n=75) and from outdoor gardens of several houses (n=25), the feces of each specimen were examined using the technique of direct examination or fresh. In 24% of these snails parasitic forms were found, such as Rhabditoide larvae of Strongyloides sp. L1 (Rhabditida: Strongyloididae) in 22 individuals, eggs of Ascaris sp. (Ascaridida: Ascarididae) in one individual, and both parasites were found simultaneously in one individual, no parasites were found in the remaining snails. Although the prevalence found was low, handling African snail may be risky to the health of the human population of this enclosure, specifically for children younger than 5 years, so it is necessary to develop health education programs in this locality.